The relationship of leg explosive power with the performance efficiency of ski racers aged 18-20 years old in competitions at various distances - Golovachev, A. I.; Kolykhmatov, V. I.; Shirokova, S. V.; Grushin, A. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to investigate the relationship between the explosive leg strength indices of 18-20 years old cross-country skiers with the performance efficiency at the main starts at different distances of cross-country ski races in the sports season 2023-2024.